3
$\begingroup$

If $A$ is a selft-adjoint operator, then the operator $U$ defined by \begin{eqnarray*} U=(A-iI)(A+iI)^{-1} \end{eqnarray*} Is unitary.

I know if $U$ is unitary then $U^{*}U=UU^{*}=I$ But when i tried to compute: \begin{eqnarray*} U^{*}U&=&{((A+iI)^{-1})}^{*}(A-iI)^{*}(A-iI)(A+iI)^{-1}\\\ &=&{((A+iI)^{-1})}^{*}(A^{*}-iI^{*})(A-iI)(A+iI)^{-1} \end{eqnarray*} or I tried to compute $UU^{*}$: \begin{eqnarray*} UU^{*}&=&{(A-iI)(A+iI)^{-1}((A+iI)^{-1})}^{*}(A-iI)^{*}\\\ &=&{(A-iI)(A+iI)^{-1}((A+iI)^{-1})}^{*}(A^{*}-iI^{*}) \end{eqnarray*} I don't know how can I continue with the hypothesis that $A$ is selft-adjoin operator and the way that I have to treat the adjoint inverse. Can you give some hint to continue? Thank you

$\endgroup$

1 Answer 1

2
$\begingroup$

HINT: Use the fact that $(S^*)^{-1} = (S^{-1})^*$ and $(iI)^* = -i I$.

$\endgroup$
2
  • $\begingroup$ But $(S^{*})^{-1}=(S^{-1})^{*}$ when $S$ is a selft-adjoint operator and bounded right? $\endgroup$ Feb 12, 2021 at 22:34
  • 1
    $\begingroup$ Since $S S^{-1} = I$, $(S S^{-1})^* = (S^{-1})^*S^* = I^* = I$. $\endgroup$
    – Falcon
    Feb 12, 2021 at 22:44

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.